Existential Approaches in Humanistic Counseling to Overcome Unfinished Business and Sense of Loneliness or Replace Loneliness: Triggers for Narcotics Use - Devi Ratnasari; Widya Anggraeni Setiarini; Aiuningtyas Yuni Oetari; Wiryo Nuryono (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Psychological problems such as loneliness and unresolved emotional conflicts (unfinished business) are increasingly recognized as important issues in modern counseling studies because they are often associated with various maladaptive behaviors, including substance abuse. This study aims to explore how an existential approach within humanistic counseling can help individuals address loneliness and unresolved emotional issues that may contribute to the risk of substance use. This research employed a qualitative case study approach to examine the counseling process and the client’s psychological experiences during existential-humanistic counseling sessions. Data were collected through in-depth interviews, observation of counseling sessions, and reflective documentation. The findings indicate that existential-humanistic counseling helps clients develop greater self-awareness, reinterpret past emotional experiences, and discover meaning in their life struggles. Through authentic therapeutic relationships and phenomenological exploration, clients were able to confront feelings of isolation and gradually resolve unresolved emotional conflicts. The counseling process also encouraged clients to take personal responsibility and develop healthier coping mechanisms when facing emotional distress. These findings suggest that existential-humanistic counseling provides a meaningful framework for helping individuals transform loneliness and unresolved emotional issues into opportunities for personal growth and psychological well-being. Keywords: existential counseling, humanistic approach, unfinished business, loneliness